The socio-economic approach to the study of main economic systems. Socialism and capitalism. Part 1. - Akulich Maria; Kaźmierczyk Jerzy (Management, 2018)
The socio-economic approach to the study of main economic systems. Socialism and capitalism. Part 1. Society is explored with the help of various approaches and methods that allow us to analyze the economy, politics, culture and society. Society as a socio-economic system can be effectively studied from the standpoint of the socio-economic approach, which is implemented within the framework of the formational approach. It was formerly used e.g. by Daniel Bell, John Kenneth Galbraith, Karl Marx, Leonid Weger, Yoshihiro Francis Fukuyama, Erik Olin Wright, and Immanuel Maurice Wallerstein. Formational approach allows us to analyze the global social and economic systems of the 20th century: capitalism and socialism. From the standpoint of this approach, the main difference between capitalism and socialism is the presence or absence of private ownership of the means of production. This feature has an impact on all aspects of social life in these systems. During the existence of these global systems, we have accumulated a rich experience of development in all areas of social life, which is analyzed in this article. The proposed article considers the positive and negative aspects of the development of capitalism and socialism. The directions of development of social and economic systems towards new form of capitalism are described and analyzed.